Implementing of Social Responsibility Standard ISO 26000 in Consumer Issues Market: Research and Consumer Protection Center -Study Case (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Abstract The aim of this research is to show the grade of implementation of ISO 26000 (Social Responsibility Standard), specifically which related in clause sex (consumer issues), this study was achieved in Market Research and Consumer Protection Center (MRCPC) / University of Baghdad. The seven consumer issues of ISO 26000 was analyzed to show the extent of its implementation in MRCPC depending of using a check list as a principle instrument to collect research data and information. Results analysis was achieved by percentages and mean average. The research was leaded some of results and the most importance one was that the grade of implementation of the center in related to consumer issues given in the standard was medium